MOKO SEBAGAI MAS KAWIN (BELIS) PADA PERKAWINAN ADAT MASYARAKAT ALOR - Putu Eka Juliawati (Forum Arkeologi, 2013)
The aims of this research are to describe the use of moko as dowry and to know the meanings of the use of moko as dowry in the life of Alor people. Data were collected by the method of observation, library research and interviews. This is a qualitative research. Data were analyzed with depth descriptive analysis and subsequently accommodated in the form of narrative. From the analysis, it is known that until this day, moko is still used as belis in which the bride grooms family has to give moko(s) to the brides family. The brides family has a right to decide what type and how many moko they want. They are opened for negotiation until both families reach an agreement. There are four meanings of the use of moko as belis that can be found namely the meaning of sacred marriage, identity, social and conservation.Tujuan penelitian ini untuk mengungkapkan penggunaan moko sebagai belis, serta untuk mengetahui makna penggunaan moko sebagai belis dalam kehidupan masyarakat Alor. Data dikumpulkan dengan metode observasi, studi pustaka dan wawancara. Data dianalisis dengan metode deskriptif analitik mendalam diakomodasikan dalam bentuk naratif. Hasil analisis ditemukan bahwa sampai saat ini dalam perkawinan adat di Alor, moko masih digunakan sebagai belis dimana keluarga laki-laki wajib menyerahkan moko kepada keluarga perempuan yang akan dilamar. Persyaratan mengenai jenis dan jumlah moko yang digunakan berada sepenuhnya di tangan keluarga pihak wanita. Negosiasi masih boleh dilakukan pihak laki-laki hingga tercapai kata sepakat. Adapun makna penggunaan moko sebagai belis adalah makna sakralitas perkawinan, makna identitas masyarakat Alor, makna sosial dan makna konservasi.